2022
DOI: 10.1039/d2ta04840j
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-stoichiometry on ion migration and photovoltaic performance of formamidinium-based perovskite solar cells

Abstract: Ion migration mechanisms are often behind degradation pathways in perovskite solar cells under operating conditions. In this work we look at the effect of non-stoichiometric compositions in mixed caesium/formamidinium inverted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The current density changes in Figure 5a under certain voltages often take minutes to stabilize [13], which coincides with the ion-migration timespan [21]. In addition, previous reports proved the A-cation halide additives in the perovskite films did increase the ionic species amount [22]. Thus, the current density change is likely related to ionic movement, which possibly affected the carrier extraction efficiency.…”
Section: Performance Degradationsupporting
confidence: 73%
“…The current density changes in Figure 5a under certain voltages often take minutes to stabilize [13], which coincides with the ion-migration timespan [21]. In addition, previous reports proved the A-cation halide additives in the perovskite films did increase the ionic species amount [22]. Thus, the current density change is likely related to ionic movement, which possibly affected the carrier extraction efficiency.…”
Section: Performance Degradationsupporting
confidence: 73%
“…The main features found in Figure 2a,b are well reproduced by the simulations: the simulated J SC and V OC match those of the measured ones within the experimental uncertainties (see Figure 1e-h) and the observed deviations are in line with those reported in most state-of-the-art optoelectronic PSCs simulation studies including ion migration. [50,[56][57][58] Therefore, they can be regarded as a sufficiently reliable basis for getting deeper insights on the different hysteretic behavior of the two mC-PSCs. By comparing the two sets of fitting parameters used to simulate the AVA-MAPbI 3 and CsPbI 3 :EuCl 3 mC-PSCs (see Table S2, Supporting Information) we find, as expected, that the most significant difference lies in the cation mobilities, that is 2 • 10 À11 cm 2 Vs À1 for AVA-MAPbI 3 and 3.7 • 10 À14 cm 2 Vs À1 for CsPbI 3 :EuCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, this can limit the bulk electronic quality of a grain (domain), since MA-I or Pb-I terminated GBs become favourable positions for the formation of defect trap states, which require additional energy of 0.5 eV and 1 eV for charge carriers to escape, respectively. 24 In parallel, an excess FAI induced non-stoichiometry study by Anta et al 25 observed a shi in the recombination mechanism (from surface dominant to bulk dominant) and high ion migration, limiting bulk electronic quality.…”
Section: Introductionmentioning
confidence: 98%